Gadai dan investasi emas: antara konsep dan implementasi - Nanda Safarida (FEBI IAIN Langsa, 2021)
Pawn services, particularly Islamic pawn services in gold (rahn) is one of Islamic banks product that distributes short term financing to consumers without repayment (qardh) in order to mutual assistance principle (tabarru’). Gold pawning services could be an alternative for consumers to get easy money and have a fast process in sharia way. Yet this gold pawning services turn to be speculative investment in practice that contrast with sharia principle and the same time it raises quention on how strong the commitment of all stakeholders to pursue the sharia principle. This study aims to analyze the concept and various problems indication in gold pawning services implementation. Descriptive analytic method is applied to analyze secondary data related to its problems. The result of the study indicate that to ensure the practice of pawning gold does not become speculative motive, it’s necessary to have a clear and binding regulations on how the pawning practice should be carried out. These regulations must also be followed by strict sanctions. In addition, ensuring the gold pawn financing is channeled to the real sector will help prevent the emergence of speculators. On the other hand, the public as customer should be aware of risks on combining product of gold pawn financing and gold investment because big profits in any investment are always followed by high risks. Finally, Participated and strong commitment of all stakeholders are the comprehensive answer in order to pursue maqasid sharia.